2022
DOI: 10.1021/acs.jafc.1c07397
|View full text |Cite
|
Sign up to set email alerts
|

Novel Temperature-Responsive Rosin-Derived Supramolecular Hydrogels Constructed by New Semicircular Aggregates

Abstract: A highly water-soluble rosin-based surfactant (C 14 -MPA-Na) was synthesized. Novel temperature-responsive supramolecular hydrogels were further prepared using C 14 -MPA-Na. The microstructure and the mechanical properties of the hydrogels were investigated. Unexpectedly, instead of the long one-dimensional structure, a new kind of twisted semicircular aggregate was formed in the hydrogels, which was rarely reported. Besides, the hydrogels possessed excellent shear-recovery properties. Upon heating to 40 °C, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This indicates that R-Lys-R forms left-handed chiral aggregates, and this chirality is different from that of the single R-Lys-R molecules and the raw materials. The phenomena of chiral aggregate formation have been extensively investigated in the literature. , For example, Hao et al . reported an amine oxide surfactant that can form chiral fibers in the presence of lithocholic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that R-Lys-R forms left-handed chiral aggregates, and this chirality is different from that of the single R-Lys-R molecules and the raw materials. The phenomena of chiral aggregate formation have been extensively investigated in the literature. , For example, Hao et al . reported an amine oxide surfactant that can form chiral fibers in the presence of lithocholic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomena of chiral aggregate formation have been extensively investigated in the literature. 46,47 For example, Hao et al 48 reported an amine oxide surfactant that can form chiral fibers in the presence of lithocholic acid. Liu et al 49 also investigated the helical nanostructures formed by (Fmoc)-protected glutamic acid triggered by purine nucleobases.…”
Section: Preparation Of the Emulsionmentioning
confidence: 99%
“…The behavior of these fibrous aggregates is different from that of the wormlike micelles, which can bend or twist at any position with any angle of their Bodies. [50][51][52][53] Comparatively, these fibrous structures are more rigid and exhibit a certain tension when bending. This may be the reason why the solution could be gelled at a very low surfactant concentration.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is difficult to self-assemble supramolecular structures in solvents only by dehydroabietic acid. By designing hydrophilic groups, our group obtained novel pH-responsive dehydroabietic acid-tailored phosphate and ammonium salt surfactants and studied their assembly behaviors in an aqueous solution. , Thereafter, Song and Zhai also obtained temperature-responsive worm-like micelles in an aqueous solution by modifying dehydroabietic acid or maleopimaric acid. …”
Section: Introductionmentioning
confidence: 93%